A 3D anisotropic visco-hyperelastic constitutive model for unidirectional continuous fiber reinforced shape memory composites. (October 2022) - Wang, Yingyu; Zhou, Helezi; Liu, Zhengkun; Peng, Xiongqi; Zhou, Huamin
Abstract: A general 3D anisotropic visco-hyperelastic constitutive model for unidirectional continuous fiber reinforced shape memory composites (SMPCs) is proposed based on energy decomposition. The total energy of SMPCs is decomposed into isotropic part from matrix and anisotropic part from fiber reinforcements, respectively. The matrix part is further decomposed into hyperelastic part and visco-hyperelastic part. Meanwhile, a temperature-dependent energy contribution weight factor is introduced to define the variation of energy contribution of matrix and fibers with phase transition in the thermodynamic process and shape memory cycle. The proposed model is demonstrated on a carbon fiber reinforced SPMC. Thermomechanical and shape memory tests of SMP and SMPCs with different fiber inclination angles are carried out and simulated with the proposed model. Comparisons between simulation results and experimental data validate the proposed model. Highlights: Proposing a general 3D anisotropic visco-hyperelastic constitutive model for unidirectional continuous fiber reinforced shape memory composites (SMPCs). The total energy of SMPCs is decomposed into isotropic part from matrix and anisotropic part from fiber reinforcements. The energy of matrix part is further decomposed into hyperelastic part and visco-hyperelastic part. Introducing a temperature-dependent weight factor to define the variation of energy contribution of matrix and fibers.